(untitled) (Latakia University Journal -Medical Sciences Series, 2019)
تناولت الدراسة مجموعة من الأطفال المقبولين في مشفى الأسد الجامعي في اللاذقية بهدف إجراء عمليات استئصال اللوزات والناميات من تاريخ 25/5/ 2005 ولغاية 25/5/2006. بلغ عدد الحالات 120، كانت معظم الحالات بين عمر 6 أشهر و6 سنوات. قمنا بتقسيم الأطفال إلى مجموعتين: مجموعة I طبق فيها التخدير الانشاقي بالهالوتان. مجموعة II طبق فيها التخدير الانشاقي بالسيفوفلوران. كان الهدف من الدراسة المقارنة بين المجموعتين من حيث سرعة المباشرة التخديرية, اختلاطات المباشرة التخديرية. بعد المقارنة حصلنا على النتائج الآتية: 1- لاحظنا تباطؤ نبض نسبي في مرض المجموعتين 2- المباشرة كانت أسرع عند تطبيق السيفوفلوران منها عند تطبيق الهالوتان. 3- لم يحدث تشنج حنجرة عند تطبيق السيفوفلوران بينما حدث تشنج حنجرة لمرة واحدة عند تطبيق الهالوتان. 4- كان الصحو سريعاً بعد إيقاف المخدر الانشاقي (السيفوفلوران) وهذه ميزة للسيفوفلوران. This study included a group of children who were accepted in Al-Assad Hospital in Lattakia to amygdalectomy and excrescences between 25 of May 2005 till 25 of May 2006. The number of cases was 120. The ages of the cases were between 6 months and 6 years. We divided the children into two groups: Group I: Halothane inhalation anesthetization was implemented. Group II: Sevoflurane inhalation anesthetization was implemented The objective of the study was to compare between the two groups with regard tothe speed in anesthetic start and complications of anesthetic. We concluded the following results from the comparison: • we noticed slow of pulse in the patients of both groups. • The start was faster in implementing Sevoflurane than implementing Halothane. • Side effects (slow of pulse, systole ecchondrosis) were less in implementing Sevoflurane than implementing Halothane. • The recovery was quick after stopping inhalation anesthetization (Sevoflurane). Tthis is a advantage for Sevoflurane.